2014
DOI: 10.1124/jpet.114.214536
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier Pharmacoproteomics-Based Reconstruction of the In Vivo Brain Distribution of P-Glycoprotein Substrates in Cynomolgus Monkeys

Abstract: The aim of this study was to investigate whether in vivo drug distribution in brain in monkeys can be reconstructed by integrating four factors: protein expression levels of P-glycoprotein (P-gp)/ multidrug resistance protein 1 at the blood-brain barrier (BBB), in vitro transport activity per P-gp molecule, and unbound drug fractions in plasma and brain. For five P-gp substrates (indinavir, quinidine, loperamide, paclitaxel, and verapamil) and one nonsubstrate (diazepam), in vitro P-gp transport activities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…Accurate and robust quantification of the OATP1A2 protein with membrane extracts of highly purified human brain capillaries will help this further. The physiologic expression data would help us to contextualize the current in vitro findings, as has been previously done for P-gp (Uchida et al, 2011a(Uchida et al, , 2014. The data could also shed light on the emerging debate on neuronal (Gao et al, 2014) and more widely accepted brain endothelial localization (Gao et al, 2000;Bronger et al, 2005;Lee et al, 2005;Kalvass et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate and robust quantification of the OATP1A2 protein with membrane extracts of highly purified human brain capillaries will help this further. The physiologic expression data would help us to contextualize the current in vitro findings, as has been previously done for P-gp (Uchida et al, 2011a(Uchida et al, , 2014. The data could also shed light on the emerging debate on neuronal (Gao et al, 2014) and more widely accepted brain endothelial localization (Gao et al, 2000;Bronger et al, 2005;Lee et al, 2005;Kalvass et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of investigators have used the cynomolgus monkey as a model to study the inhibition of drug transporters in vivo (Tahara et al, 2006;Shen et al, 2013Shen et al, , 2015bTakahashi et al, 2013;Uchida et al, 2014;Chu et al, 2015;Karibe et al, 2015). Such a model offers advantages in drug development, when the transporter inhibition potential of a clinical candidate requires more extensive evaluation of changes in victim drug pharmacokinetics and organ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has revealed interspecies differences in the overall impact of P-gp at BBB of rodents and primates (Syvänen et al, 2009;Tournier et al, 2012). As opposed to rodents, recent proteomic studies have confirmed that monkeys may serve as a robust animal model of drug distribution in the human brain (Uchida et al, 2014).…”
Section: Introductionmentioning
confidence: 97%